Raw Material Control In The Framework Of Achieving Targets Production In Trading Business (UD) Naga Mas - Nurtanti Nurtanti; Muh Rizal S; Syarifuddin Syarifuddin; Nurhasni Muis; Andi Mahdiana Mardatillah (Jurnal Administrasi Bisnis, 2026)
This study aims to know and analyze the control of raw material inventories in order to achieve UD Naga Mas production targets. To achieve this study, the study used a qualitative method, taking 3 (three) respondents consisting of owner, warehouse division employee, and administrative division employee. The data collection procedures used are in-depth interviews and documentation. Interview techniques are conducted in a structured manner using interview guidelines. The results of the research showed that UD Naga mas company in carrying out the control of raw material inventories is not based on theory but based on the situation and conditions of the company which can be said to be quite good and effective because it carries out control of raw material inventories based on the company's practices and calculations.